Seed colour- not a diagnostic character for disease resistance in linseed (Linum usitatissimum L.) - O. PRAKASH and M. VAJPEYI, JYOTI SINGH*, K. SINGH (Indian Phytopathology, 2006)
Linseed (Linum usitatissimum L), a commercially important oilseed crop was studied for the correlation between seed colour and disease resistance. The brown seeded germplasm were found more tolerant to diseases than fawn and yellow seeded ones. The majority of the resistant lines were brown seeded and yellow seeded lines were mostly susceptible to diseases particularly against wilt. Yellow seeded germplasm contained higher oil content and a highly significant positive correlation was recorded between oil content and the wilt percentage. However, there were exceptions as many brown seeded lines were highly susceptible to diseases and some of the yellow seeded lines viz., KL-1, KL-209, KL-210, LC-2166 and LC-2178 were tolerant. The data therefore, suggested that the seed colour and oil content may be one of the components conferring disease resistance but resistance against diseases is a genetic character. The phenotypic characters like seed colour may be the primary indicator but it can not be the diagnostic character.